Representasi Citra Event Ittiba’ pada Konten Testimoni di Instagram @ynevent.id - Rizki Ahmad Nur Fauzi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
Instagram has become one of the social media platforms widely utilized in digital da’wah activities, not only as a medium for conveying religious messages but also as a tool for shaping the image of event organizers through visual and narrative content. Along with the increasing use of social media, communication strategies based on participant testimonials have emerged as an effective form of message presentation in building public perception. This study aims to analyze how the image of the Ittiba’ Event is represented through participant testimonial content on the Instagram account @ynevent.id using Frank Jefkins’ image theory.The research employs a descriptive qualitative approach through visual and textual content analysis of five testimonial video posts with the highest levels of interaction based on the number of likes and comments. Each piece of content is analyzed to identify the presence of the five image categories proposed by Jefkins, namely current image, experience image, mirror image, wish image, and multiple image. The findings indicate that all Jefkins’ image categories appear in the testimonial content, namely: (1) current image, reflected through participants’ enthusiasm, sense of closeness, and emotional responses; (2) experience image, shown in participants’ direct experiences during the event; (3) mirror image, related to how participants perceive the identity and reputation of @ynevent.id; (4) wish image, referring to the expected benefits, religious values, and spiritual impact; and (5) multiple image, which emerges from the combination of perceptions held by participants, organizers, speakers, and the visual presentation on the @ynevent account. This study concludes that testimonial content on Instagram plays a significant role in building a positive image of the Ittiba’ Event. Future research is recommended to conduct comparative analyses across different events or to expand data sources to other digital platforms.